PENGARUH PSYCHOLOGYCAL FIRST AID TERHADAP TINGKAT KECEMASAN DAN TRAUMA POST HIGH CASE PANDEMI COVID-19 - Diah Priyantini; Septian Galuh Winata; Erfan Rofiqi; Chlara Yunita Prabawati (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:  This study aimed was to search the effectiveness intervention psychological first aid to anxiety and post high case COVID-19 trauma. Methods:  A quasy experiment study with two groups consisting of 110 respondents was recruited using purposive sampling. Independent variable was the psychological fisrt aid intervention, the instrument used the media module. Dependent variable consists of anxiety that measured with depression anxiety stress scale 21 and COVID-19 post pandemic trauma measured with crisis mental health emergency questionnaire. Data were analyzed using SPSS version 21 with the Wilcoxon Signed Rank Tests. Results:  The results of the significance test showed that psychological fisrt aid had a significant effect on anxiety (p = 0.001) and post high case COVID-19 trauma (p = 0.000). The anxiety and post high case COVID-19 trauma  showed better change in intervention group than control group Conclusion: Psychological first aid interventions for respondents with anxiety and trauma after the high case of COVID-19 showed a significant effect. Psychological first aid in dealing with post high case anxiety and trauma of COVID-19 can focus on the principle of look, listen and link to integrate the intervention process from the largest unit to the smallest unit, so that the intervention has a direct impact on patients in improving their psychological condition. experienced by the patient.